2019
DOI: 10.1002/jqs.3171
|View full text |Cite
|
Sign up to set email alerts
|

Glacier Peak and mid‐Lateglacial Katla cryptotephras in Scotland: potential new intercontinental and marine‐terrestrial correlations

Abstract: Using contiguous high resolution sampling methods, we report the detection of a Glacier Peak volcanic ash from North America in Lateglacial Interstadial lake sediments in western Scotland. It occurs in close proximity to the Icelandic Borrobol and Penifiler tephras, but is distinguishable by its rhyolitic major‐element composition that is consistent with the earliest set G layer, one of a number of mid‐Interstadial Glacier Peak eruptions dated between 13.71 and 13.41 cal ka bp. Another cryptotephra layer prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…(2020) have already shown that the Azores can be a source, and two further papers show that even more distant volcanic regions have contributed tephras to the British Isles tephra framework. Firstly, Pyne‐O'Donnell and Jensen (2020) re‐examine cores from Loch Ashik, Scotland, first investigated by Pyne‐O'Donnell (2004, 2006), at a high resolution and uncover evidence for North American tephra deposition (Glacier Peak G) at this site during the Lateglacial Interstadial. Secondly, through their investigation of early‐ to mid‐Holocene sediments from Llyn Llech Owain, Wales, Jones et al .…”
Section: Theme 3: Applications Of Tephrochronology Around the Globementioning
confidence: 99%
“…(2020) have already shown that the Azores can be a source, and two further papers show that even more distant volcanic regions have contributed tephras to the British Isles tephra framework. Firstly, Pyne‐O'Donnell and Jensen (2020) re‐examine cores from Loch Ashik, Scotland, first investigated by Pyne‐O'Donnell (2004, 2006), at a high resolution and uncover evidence for North American tephra deposition (Glacier Peak G) at this site during the Lateglacial Interstadial. Secondly, through their investigation of early‐ to mid‐Holocene sediments from Llyn Llech Owain, Wales, Jones et al .…”
Section: Theme 3: Applications Of Tephrochronology Around the Globementioning
confidence: 99%
“…Tephra shards that mark volcanic ash layers serve as a powerful chronological tool, enabling the refinement of tephrochronological age uncertainties and provide reliable isochronous tephrostratigraphic tie-points. Widely dispersed tephra from highly explosive eruptions help to facilitate precise temporal comparisons between palaeoenvironmental records over regional to continental scales 9 , 10 . Tephra layers are a particularly useful chronological tool when: (1) glass shards can be confidently correlated to a volcanic centre and/or eruption through chemical compositions 11 ; (2) they are widely dispersed and provide tie-points in important records 12 ; (3) well dated by absolute and relative dating techniques 13 , 14 and; (4) they can be linked to a climatic/archaeological event or transition around the time of the eruption 8 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Tephra shards mark volcanic ash layers and serve as a powerful chronological tool, enabling the re nement of tephrochronological age uncertainties and providing isochronous tephrostratigraphic tiepoints. Widely dispersed tephra from highly explosive eruptions help to facilitate precise temporal comparisons between palaeoenvironmental records over continental to regional scales [9,10] . Tephra layers are a particularly useful chronological tool when: 1) glass shards can be con dently correlated to a volcanic centre and eruption through chemical compositions [11] ; 2) they are widely dispersed that lead to tie-points in records at regional and global scales [12] ; 3) well dated by absolute and relative dating techniques [13,14] and; 4) they are linked to a climatic/archaeological event or transition around the time of the eruption [8,15] .…”
Section: Introductionmentioning
confidence: 99%